Answer:
-24 a^2 b^7
Step-by-step explanation:
Simplify the following:
-8×3 a^2 b^4 b^3
Hint: | Combine products of like terms.
3 a^2 b^4 (-8) b^3 = 3 a^2 b^(4 + 3) (-8):
-8×3 a^2 b^(4 + 3)
Hint: | Evaluate 4 + 3.
4 + 3 = 7:
-8×3 a^2 b^7
Hint: | Multiply 3 and -8 together.
3 (-8) = -24:
Answer: -24 a^2 b^7
Answer:
3
Step-by-step explanation:
V=(4/3)(pi)(r^3)
V=(4/3)(pi)(8^3)
V=(4/3)(pi)(512)
V=(2048/3)(pi), or around 2144.660585
$60 ÷ $15 = 4
$9 × 4 = $36
he saved $36 when he earned $60
Eddie: $10-3=$7
Marsha: $8+$3=$11